SPECTRAL ANALYSIS AND PHYSICAL PROPERTIES OF MAIN- SEQUENCE STARS - Al-Abudi, Bushra; Hussain, Ali; Abdulla, Ashraf (Iraqi Journal of Science, 2024)
The analysis of stellar spectrum was considered as an efficient tool for studying the chemical composition of stars and measuring the physical properties. In this paper, we selected four stars of the main- sequence band namely (HD 6111, HD 221741, SU Aur, HD 5351) for analyzing their spectra. The chemical composition of each star can be extrapolated from their own absorption spectrum by comparing their positions in the spectrum with those observed from pure source in the laboratory, while from the emission spectra, we measured the physical properties including, temperature, mass, radius, velocity, and lifetime. The results indicated that the selected stars of the main sequence have the chemical composition hydrogen, ionized helium, Fe, C, Si, . Our calculations of the stars under investigation give rise to the following physical properties, their surface temperature between (4983 – 8130K), mass between (0.74 – 2 Ms), radius between (0.795 - 1.77 Rs), luminosities between (0.35 - 10) and lifetime between (2 – 20 Gy)